Strategic Leadership of School Principals in Enhancing Character Education in the Digital Literacy Era - Dhanu Lukmantoro; Nunuk Hariyati; Yatim Riyanto; Sri Setyowati (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research aims to explore the strategies employed by school principals to enhance character education through digital literacy at 3rd Sidoarjo State Senior High School, providing detailed insights into goal-setting processes and strategies. Method: The study utilizes a qualitative approach, involving informants such as school principals, vice principals, subject teachers, and education staff. Data collection includes interviews, field notes, and other relevant materials. Systematic data analysis is performed by categorizing, synthesizing, and identifying patterns to derive meaningful findings. Results: The findings reveal significant positive impacts on students, teachers, parents, and the school environment. Students show improved discipline, reduced delinquency, and enhanced digital responsibility. Teachers display better attendance and a deeper understanding of their role as role models. Increased parental involvement in school activities fosters a collaborative atmosphere. The school's management and community engagement have also improved, contributing to a supportive educational environment. Novelty: This study uniquely integrates character education with digital literacy, demonstrating a holistic approach to educational enhancement. It highlights the interconnectedness of ethical digital behavior and character development, offering a comprehensive model for other schools to emulate. The research underscores the importance of continuous evaluation and the inclusion of diverse perspectives to sustain and evolve effective character education programs in the digital age.